2003
DOI: 10.1152/jn.00105.2003
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Synaptic Plasticity in the Lateral Perforant Path Input to the Dentate Gyrus of Aged C57BL/6 Mice

Abstract: Hippocampal slices obtained from C57BL/6 mice (3-25 mo) were used to investigate the effects of aging on excitatory postsynaptic potentials (EPSPs) elicited in dentate gyrus with lateral perforant path stimulation. The maximal amplitude of the EPSP, as well as the degree of paired-pulse facilitation, was significantly reduced in animals aged 12 mo or more compared with younger animals (<12 mo). Although all animals showed equivalent short-term potentiation (STP) in response to high-frequency stimulation, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 69 publications
4
28
1
Order By: Relevance
“…Likewise, the outer molecular layer exhibits accelerated synaptic loss in AD models [59]. The perforant path projection to the dentate gyrus also shows selective deficits in synaptic plasticity in AD models [60] and in normal aging [61]. Overall, these data demonstrate that the perforant path projection arising from neurons in layer II of the entorhinal cortex is particularly susceptible to molecular and functional alterations with aging and AD.…”
Section: Circuit Susceptibility With Aging and Ad: Evidence For Trmentioning
confidence: 99%
“…Likewise, the outer molecular layer exhibits accelerated synaptic loss in AD models [59]. The perforant path projection to the dentate gyrus also shows selective deficits in synaptic plasticity in AD models [60] and in normal aging [61]. Overall, these data demonstrate that the perforant path projection arising from neurons in layer II of the entorhinal cortex is particularly susceptible to molecular and functional alterations with aging and AD.…”
Section: Circuit Susceptibility With Aging and Ad: Evidence For Trmentioning
confidence: 99%
“…The exact nature of the underlying neuronal changes that give rise to these age-related deficits remains unknown; however, there is mounting evidence that one brain region-the hippocampus-seems to be particularly sensitive to aging and is thought to be responsible, at least in part, for the age-related cognitive decline that occurs during normal aging [6]. Many age-related changes within the hippocampus have been documented, including altered mitochondrial function [7], oxidative stress [8], and alterations in glutamate transmission [9] and synaptic plasticity [10,11]. Hence, an important aspect of aging research has been the quest for treatments that will prevent or ameliorate the memory deficits associated with aging.…”
mentioning
confidence: 99%
“…Some of the first evidence for perforant path impairments in aged animals was obtained in rats, where it was found that perforant path transmission to dentate gyrus granule cells was impaired, as well as long-term potentiation (Barnes and McNaughton, 1980; Barnes et al, 2000). Additional studies provided further support for these age-related impairments (Froc et al, 2003; Krause et al, 2008) and showed additional deficits, such as reduced synaptophysin expression in perforant path terminals in aged animals (Smith et al, 2000). Also, there were deficits in activation of proteins involved in synaptic plasticity in granule cells, such as Arc (Chawla and Barnes, 2007; Penner et al, 2010).…”
Section: Ec Neurons Are Also Vulnerable In Other Diseasesmentioning
confidence: 94%